ANALISIS PERENCANAAN PENGELOLAAN DANA DESA PADA DESA MAJANGAN KABUPATEN SAMPANG - Makromah, Siti; Junjunan, Mochammad Ilyas (Universitas Prof.Hazairin,SH Bengkulu, 2025)
This study aims to analyze the planning and management of Village Funds in Majangan Village, Sampang Regency, during the 2023–2025 period. The main focus is to examine how the village government plans the use of Village Funds to remain effective and aligned with community needs amid limited budgets and environmental challenges. This research employs a qualitative descriptive method. Data were collected through in-depth interviews with the Village Head and village officials, documentation of the Village Government Work Plan (RKPDes) and the Village Budget Realization Report (APBDes), as well as direct field observations of development activities. The findings indicate that the planning process of the Village Fund is carried out through a participatory mechanism known as Musyawarah Desa (Village Deliberation), which allows community involvement in determining development priorities. Most of the Village Fund is allocated to the field of village development, particularly infrastructure projects such as roads, irrigation, and street lighting. The management of the Village Fund in Majangan Village reflects the principles of transparency, accountability, and community participation. Although there was a decline in fund allocation in 2025, the village government successfully maintained financial balance and implemented priority programs in accordance with prevailing regulations.